2012
DOI: 10.1242/jeb.077016
|View full text |Cite
|
Sign up to set email alerts
|

Lipid composition of the stratum corneum and cutaneous water loss in birds along an aridity gradient

Abstract: SUMMARYIntercellular and covalently bound lipids within the stratum corneum (SC), the outermost layer of the epidermis, are the primary barrier to cutaneous water loss (CWL) in birds. We compared CWL and intercellular SC lipid composition in 20 species of birds from desert and mesic environments. Furthermore, we compared covalently bound lipids with CWL and intercellular lipids in the lark family (Alaudidae). We found that CWL increases in birds from more mesic environments, and this increase was related to ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Rates of cutaneous water loss (CEWL) in birds are regulated in part by adrenergic control of venous blood flow to the skin in response to heat stress (Ophir et al 2002) and as such are not completely passive, but the metabolic costs of modulating CEWL seem to be negligible (Marder and Ben-Asher 1983;Marder and GavrieliLevin 1987). The permeability of the skin to water is directly related to the relative quantity and structure of the lipids in the stratum corneum, which varies with environmental aridity and among phylogenetic classes of birds (Haugen et al 2003;Ro and Williams 2010;Muñoz-Garcia and Williams 2011;Champagne et al 2012). The specific mechanisms that columbiforme birds use to greatly enhance cutaneous evaporation at high temperatures have not received as much attention Hoffman and Walsberg 1999;McKechnie and Wolf 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Rates of cutaneous water loss (CEWL) in birds are regulated in part by adrenergic control of venous blood flow to the skin in response to heat stress (Ophir et al 2002) and as such are not completely passive, but the metabolic costs of modulating CEWL seem to be negligible (Marder and Ben-Asher 1983;Marder and GavrieliLevin 1987). The permeability of the skin to water is directly related to the relative quantity and structure of the lipids in the stratum corneum, which varies with environmental aridity and among phylogenetic classes of birds (Haugen et al 2003;Ro and Williams 2010;Muñoz-Garcia and Williams 2011;Champagne et al 2012). The specific mechanisms that columbiforme birds use to greatly enhance cutaneous evaporation at high temperatures have not received as much attention Hoffman and Walsberg 1999;McKechnie and Wolf 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Ceramide II, the more polar group of ceramides, and cerebrosides increased at a greater rate with depth in winter birds than in summer birds, indicating that these lipids play an instrumental role in reducing CWL, especially in the deeper levels of the SC. More polar lipids have been correlated with lower rates of CWL in birds (Haugen et al, 2003;Muñoz-Garcia et al, 2008a,b;Champagne et al, 2012).…”
Section: Lipidsmentioning
confidence: 99%
“…The composition and attendant organization of these lipid classes affects the rate of CWL . Previous studies on birds have found that higher amounts of free fatty acids and triacylglycerols within the SC are associated with higher rates of CWL, whereas more polar ceramides and cerebrosides are associated with lower rates of CWL (Haugen et al, 2003;Muñoz-Garcia et al, 2008a,b;Champagne et al, 2012). Cerebrosides are thought to be especially important in regulating CWL, as they account for approximately one-third of all lipids in the SC in birds, and occur in greater amounts in the SC of birds acclimated to cold, dry conditions than in birds acclimated to warmer, more humid conditions (Muñoz-Garcia et al, 2008a).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations